Experiments on pitch perception: Implications for music and other processes - HOUTSMA, Adrianus J.M. (Archives of Acoustics, 2007)
This paper presents a review of the development of our understanding of pitch perception during the past three decades, in which the author was deeply involved. Some specific applications are discussed that are for the most part in the domain of music perception and show where the interest in pitch perception has led us today.